(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Skin diseases are a common problem faced by people worldwide, and there is a growing demand for natural and safe solutions to treat them. Nanogels are a promising drug delivery system due to their small size, high surface area, and ability to encapsulate both hydrophilic and hydrophobic compounds. In this study, we aimed to optimize and evaluate the parameters of a herbal-based nanogel formulation for the treatment of skin diseases. The nanogel formulation was prepared using a combination of natural polysaccharides, namely chitosan and sodium alginate, and a herbal extract of neem leaves. The optimization parameters included varying the concentrations of chitosan, sodium alginate, and neem extract, and the pH of the formulation. The optimized formulation was evaluated for its physicochemical properties, drug release profile, stability, and skin irritation potential. The results showed that the optimal nanogel formulation had a particle size of 200 nm, a zeta potential of +25 mV, and a drug entrapment efficiency of 80%. The drug release profile was found to be sustained, with 60% of the drug being released over 8 hours. The stability studies showed that the formulation was stable for 3 months at 4°C. The skin irritation studies indicated that the nanogel formulation was non-irritating and safe for topical application. The herbal-based nanogel formulation developed in this study has the potential to be a safe and effective treatment option for skin diseases. Further studies are required to investigate its efficacy in vivo and in clinical trials.